Peristiwa Malari 1974: Pergeseran Narasi dari Gerakan Moral ke Stigma Politik dalam Propaganda Orde Baru - Ganda Febri Kurniawan; Alfira Apriyanti (Perkumpulan Program Studi Sejarah Se-Indonesia, 2026)
The Malari incident on January 15, 1974, was a pivotal moment in Indonesian political history, marking tensions between students, community groups, and the New Order government. This study aims to analyze the factors that triggered Malari, the dynamics of student action, and the government's response within the context of political stability and economic development. The research method used is historical, with an analytical approach to documents, newspaper archives, and secondary literature related to economic and political policies at the time. The results show that Malari was not simply a protest against foreign investment but also reflected a critique of corruption, social injustice, and the political control of the New Order. Furthermore, this event reveals patterns of interaction between student moral movements and the political stigma that the government constructs through propaganda. This study provides a new perspective in understanding Malari as a complex socio-political phenomenon, while also emphasizing the role of students as agents of change amidst the pressures of an authoritarian regime.